Some aspects of gene dosage effects in N-type sheep : a thesis submitted in part fulfilment of the degree of Master of Science, Massey Agricultural College - Stephenson, S K (Massey University, 1952)
A study of gene dosage effects in N-type sheep has been made using the fibre type array method and the medullometer method developed by Elphick and McMahon. As the position was complicated by gradients occuring in the fibre type arrays and total fleece medullation over the body, the study on each sheep was made in the seven positions: back, withers, side, shoulder, shoulder patch, neck and britch, this being to see what gradients were present and how these changed with increasing N-gene dosage.
No abstract supplied. First paragraph of summary used as an abstract.
Keywords: Sheep; Breeding; Drysdale sheep; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Animal production::Animal breeding